Case Report: Rapidly Progressive Interstitial Lung Disease in A Pregnant Patient With Anti-Melanoma Differentiation-Associated Gene 5 Antibody-Positive Dermatomyositis - Chen, Cuihong; Chen, Yulan; Huang, Qin; Hu, Qiu; Hong, Xiaoping (Frontiers in Immunology, 2021)
Dermatomyositis occurs extremely rarely during pregnancy. A number of studies in the published literature have documented how the outcome of pregnancy is poor for both mother and fetus. The present case study reports on a patient who was diagnosed with clinically amyopathic dermatomyositis complicated by interstitial lung disease during pregnancy, and was successfully treated with a combined immunosuppressant regimen. To the best of the authors’ knowledge, this is the first case study detailing how a pregnant woman with clinically amyopathic dermatomyositis (CADM) with positive anti-melanoma differentiation-associated gene 5 (MDA5) antibody achieved complete remission after early intervention of combined immunosuppressive therapy without residual pulmonary interstitial changes.